Bad influence: social networks, elite brokerage, and the construction of alliances. (September 2020) - Sazak, Selim Can
If all states want to survive, why do some of them enter unpropitious alliances? International Relations (IR) theory's conventional answer is that imperfect information and systemic complexity result in miscalculation. This explanation begs the question: any alliance that fails is a miscalculated one, so the puzzle is not whether but why such mistakes are made. This article imports from recent scholarship on network theory and interpersonal trust to offer an alternative explanation. Alliances are not entities ethereally formed out of strategic imperatives, but products of interactions within transnational social networks of political, military, and business elites in the prospective allies. Such interactions enable alliances because people who are connected to each other through mutual association or previous exchanges develop mutual trust and gain subjective certainty about each other's intentions and capabilities, which points at a previously ignored mechanism in alliance behavior: brokerage. In a case study that combines theory-based archival research and social network analysis, this article uses historical evidence on the Turco-German alliance to empirically demonstrate the brokerage role Colmar von der Goltz, the head of the German military mission to the Ottoman Empire, played in the two countries' relations at the turn of the century and their eventual alliance in the First World War. The analysis points at a potential means of bridging IR, history, and sociology while expanding our understanding of alliance behavior and providing policy-relevant insights on geo-economic competition and the weaponization of interdependence at a time of growing strategic rivalry on the world stage.